The Cost of Contraception in the United States - Salcedo, Jennifer; Kaneshiro, Bliss (Current Women's Health Reviews, 2014)
Use of any form of contraception results in cost-savings compared to non-use of contraception, regardless of payer type. Long-acting reversible contraceptive (LARC) methods are significantly more cost-effective than short-term hormonal and barrier methods, even when LARC methods are not used for their full duration of efficacy. Despite increased contraceptive coverage and reduced patient cost-sharing under the Affordable Care Act, significant barriers remain in addressing the unmet need for effective contraception and fully realizing the decreased health care costs associated with use of contraception in the United States.
Keywords: LARC